2005
DOI: 10.1007/s00436-004-1283-5
|View full text |Cite
|
Sign up to set email alerts
|

The contamination of wild watercress with Fasciola hepatica in central France depends on the ability of several lymnaeid snails to migrate upstream towards the beds

Abstract: As most natural watercress beds in central France are located upstream of the permanent habitats of two lymnaeid species, Galba truncatula and Omphiscola glabra, field investigations were made from 1999 to 2004 on 67 beds to determine why the contamination of watercress with Fasciola hepatica is irregular over time in these sites, while definitive hosts, especially lagomorphs, are regularly found infected around them. Snails are able to migrate upstream in winter and spring towards the beds, and a 4-year surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 6 publications
(5 reference statements)
0
16
0
12
Order By: Relevance
“…The only zoonotic helminths linked to fresh produce are the trematodes Fasciola hepatica and gigantica, Fasciolopsis buski, and the nematodes Ascaris suum, Toxocara canis and cati, Toxascaris leonine, Lagochilascaris minor, and both Angiostrongylus cantonensis and costaricensis (Polley, 2005;Slifko et al, 2000). Only Fasciola hepatica has been responsible for outbreaks of produce-borne infections in humans (Macpherson, 2005;Mas-Coma, 2005;Rondelaud et al, 2005).…”
Section: Parasitic Pathogensmentioning
confidence: 99%
See 2 more Smart Citations
“…The only zoonotic helminths linked to fresh produce are the trematodes Fasciola hepatica and gigantica, Fasciolopsis buski, and the nematodes Ascaris suum, Toxocara canis and cati, Toxascaris leonine, Lagochilascaris minor, and both Angiostrongylus cantonensis and costaricensis (Polley, 2005;Slifko et al, 2000). Only Fasciola hepatica has been responsible for outbreaks of produce-borne infections in humans (Macpherson, 2005;Mas-Coma, 2005;Rondelaud et al, 2005).…”
Section: Parasitic Pathogensmentioning
confidence: 99%
“…Human infection with F. hepatica in developed countries is almost exclusively due to ingestion of contaminated aquatic vegetation; primarily watercress (Macpherson, 2005;Rondelaud et al, 2005), and a number of aquatic plant-borne infections of F. hepatica have been reported . The primary routes of exposure to humans in developing countries are contaminated drinking water and food.…”
Section: Helminthsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors (Økland, 1990;Moens, 1991;Vareille-Morel et al, 1999) have already reported the marginalization of most G. truncatula habitats at the peripheral extremity of open drainage and rainwater-draining furrows. According to these authors, G. truncatula was outcompeted by other lymnaeids, including O. glabra which may even drive G. truncatula to local extinction (Rondelaud et al, 2005). Our results demonstrate that A. hypnorum also exerted an evident negative effect on O. glabra, though to a lesser extent than on G. truncatula because of the two following reasons: (i) the complete colonization of O. glabra habitats by the physid took longer than that of the other lymnaeid (7 years instead of 4 years, respectively: Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Der Mensch ist ein "Gelegenheitswirt". Die Aufnahme erfolgt durch an Grashalmen oder Gemüse enzystierte Erregerstadien oder durch das Garnieren von Speisen mit kontaminierten Gewürz-gräsern wie Brunnenkresse [9,13] …”
Section: Leberegelunclassified